QUALITY OF FRESH-CUT PAPAYA ‘GOLDEN’ STORED AT DIFFERENT TEMPERATURES - OLIVEIRA JR, Luiz Fernando Ganassali; CARLOS, Lanamar Almeida; CORDEIRO, Carlos Alberto Martins; COELHO, Enilce Maria; ARAÚJO, Thiago Rezende (Scientia Agraria, 2007)
This research studied the effect of storage temperature on the preservation of fresh-cut papaya. The papaya, previously cooled to a temperature of 6 ºC, were selected, washed, sanitized, cuted in cubs, rinsed, and stored in plastic packaging of low density polyethylene rigid, and then stored at 5 and 10 ºC for 8 days. The following aspects were evaluated: pH, titratable acidity, soluble solids, vitamin C and microbiological in the fresh-cut papaya. The experimental design was completely randomized, with three repetitions. The titratable acidity was lower with the highest temperature. The analysis for the vitamin C and pH, did not presented significant variation between the temperatures and days of storage The total soluble solids content did not vary between treatments, and hygienic care adopted during processing allowed to obtain low microbial counting products, in chunks stored at 5 oC after 8 days. These results allow to indicate papaya for fresh-cuts production, in chunk form, with refrigerated conservation (5 oC) for 8 day periods.